Voting at 16 – Lessons for the Future from the Scottish Referendum. Issue 1 (February 2017) - Hill, Malcolm; Lockyer, Andrew; Head, George; McDonald, Craig A.
Abstract : The 2014 Referendum on Scottish independence raised many issues about the future of Scotland. It also produced an innovation as regards the electoral process by making 16 years the minimum age of participation. This article examines issues surrounding the voting age and draws on a schools-based study, which shed light on teacher and pupil opinion about this lower than usual threshold for voting. It is also concerned with how schools cover the teaching of politics and prepared students for the Referendum debate within a context of expected neutrality on a highly divisive matter. Some implications of extending the lower voting age for future elections are discussed.